Pelanggaran Hukum Laut Internasional dalam Konflik Selat Hormuz: Tindakan Iran, Amerika Serikat dan Problematika Penegakan Hukum Internasional - faisal syafri azmi (Jurnal Hukum Lex Generalis, 2026)
The escalation of the US-Iran conflict since February 2026 has made the Strait of Hormuz a center of international maritime law dispute. This normative legal research employs statute, case and conceptual approaches to analyze both states' violations of international law and the failure of enforcement mechanisms. The findings indicate that Iran's actions contravene UNCLOS norms—partially recognized as international customary law—including discriminatory navigation practices and restrictions on transit passage rights. Meanwhile, the United States violates Article 2(4) and Article 51 of the UN Charter through unilateral blockade without UN Security Council mandate and misuse of self-defense rights. International law enforcement fails due to ITLOS jurisdiction limitations and UN Security Council deadlock caused by the veto power. This condition creates a legal vacuum that places power above law in international dispute resolution.